PROFIL MASYARAKAT COMMUTER DI DUSUN SUNGAI SIBAM DESA KARYA INDAH KECAMATAN TAPUNG KABUPATEN KAMPAR - Helen Puspita Sari; Yonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to know the profile of the commuter society, social relations and commuter society activities in the Sibam River subdistrict of Tapung Kampar regency. This research uses descriptive quantitative method based on distribution of limited questions according to the theory that used. The subject of this study is specified by cluster sampling. This method is a technique of sampling in the form of special units such as religions, groups, tribes, nations. Cluster sampling did not choose individual as sample unit, but chose groves population as a member unit of the population based on the division of neighbourhood groups of commuter society who lives in the Sibam river as many as 65 commuters. The result of this research shows that the mostly of commuter have been domiciled in the hamlet of Sibam River. The commuter society profile is very diverse in terms of social background, economic aspects and the ownership of the asset. the pattern of public relations in commuter society is mechanics solidarity. There is a positive relations between commuter society with neighbors that called primary social relations. Then, relations between commuter with workers and with the chief in work place arguably the secondary social relations.Keywords: Profile, Commuter Society, Activity